Challenges and efforts of modern Chinese urban women in romantic relationships in Happy Home Magazine (1936-1949) - Yang, Lan; Azlizan Mat Enh,; Suffian Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The aim of this article is to explore the challenges, efforts, and effects of urban women’s romantic relationships through an analysis of the modern Happy Home magazine in China. Happy Home magazine documented the love and marriage lives of urban women in China in the 1930s and 1940s. In feudal China, parents’ arranged marriages led to obstacles to women’s romantic relationships. In modern times, the Western idea of free love and marriage was introduced to China, and women rushed into the flood of free love. However, in the process of falling in love, women still face a series of challenges, such as the single criterion for choosing a spouse, the narrow socialization range, and the restriction on the age of choosing a spouse. In order for women to effectively practice free love, Happy Home magazine guides women to use a variety of ways to courageously fall in love freely and strive for their own happiness. For example, improving the criteria for choosing a spouse, expanding women’s socialization, upgrading their own qualities, actively seeking a partner and improving their ability to resist falling out of love, and so on. This not only enhances women’s ability to fall in love, but also raises women’s awareness of their autonomy, and is conducive to the promotion of equality between men and women and the improvement of women’s social status.